Peran Teori Keadulatan Tuhan pada Perang Kediri dan Tumapel pada Pembentukan Hukum di Indonesia - Sarip Sarip (Universitas Muhammadiyah Purwokerto, 2020)
The sovereignty of God in the state administration of the Kingdom of Indonesia can be seen from the words of Ken Arok attacking the kingdom of Kediri,